SIRÈNES ET AUTRES ONDINES : REPRÉSENTATIONS MÉDIÉVALES DES FIGURES AQUATIQUES SCANDINAVES - D’INCA, Elise (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Mermaids and Other Undines: Medieval Representations of Scandinavian Aquatic Figures. Without claiming to be exhaustive, this article compares the different aquatic figures of Scandinavian imagination, and the representations relating to Scandinavia, taking into account their cosmic aspect. This paper highlights the close connection of these creatures with time, weather and music, and the evolution of the representation of sea creatures that embody geography and climate, real or fantasized. These representations evolve, especially because of the important Christianization process that they undergo. With Christianization, these sea creatures tend towards demonization, and they’re influenced by Occidental representations, especially with those of the sirens of the Nibelungenlied. Scandinavian aquatic figures represent different dangers according to the type of water in which they live: salty, soft or marshy. According to their gender, the marine creatures which embody different risks are put in perspective in a comparative approach that links the Eddas and the stories reported by Xavier Marmier, especially Danish and Swedish. Thanks to the privileged bond these figures, emerging from the Edda, sagas and ballads, maintain with speech and music, their evolutions and their representations survive in the collective imagination related to Scandinavia. REZUMAT. Sirene și alte ondine: reprezentări medievale ale figurilor acvatice scandinave. Fără a pretinde a fi exhaustiv, acest articol compară diferitele figuri acvatice ale imaginarului scandinav și reprezentările referitoare la Scandinavia, ținând cont de aspectul lor cosmic. Lucrarea de față evidențiază legătura strânsă a acestor creaturi cu timpul, vremea și muzica, precum și evoluția reprezentării creaturilor marine, reale sau imaginare, care întruchipează geografia și clima. Odată cu creștinizarea, aceste creaturi marine tind spre demonizare și sunt influențate de reprezentările occidentale, mai ales de cele ale sirenelor din Cântecul Nibelungilor. Figurile acvatice scandinave se disting după pericolul pe care îl reprezintă și după tipul de apă în care trăiesc: sărată, dulce sau mlăștinoasă. Creaturile marine care întruchipează diferite riscuri sunt analizate în funcție de tipologiile enunțate, printr-o abordare comparativă care leagă Edda și poveștile transmise de Xavier Marmier (în special de origine daneză și suedeză). Datorită legăturilor lor privilegiate cu limbajul și muzica, aceste figuri din Edda, saga și balade supraviețuiesc în imaginarul colectiv scandinav. Cuvinte-cheie : Evul mediu, literatură scandinavă, reprezentări hibride, sirenă, imaginarul apei Article history: Received 2 February 2023; Revised 28 April 2023; Accepted 30 May 2023; Available online 23 June 2023; Available print 30 June 2023.